Ouabain inhibits placental sFlt1 production by repressing HSP27‐dependent HIF‐1α pathway. Issue 10 (26th June 2014) - Rana, Sarosh; Rajakumar, Augustine; Geahchan, Carl; Salahuddin, Saira; Cerdeira, Ana Sofia; Burke, Suzanne D.; George, Eric M.; Granger, Joey P.; Karumanchi, S. Ananth
Abstract : Up‐regulation of placental soluble fms‐like tyrosine kinase 1 (sFlt1) contributes to the pathogenesis of preeclampsia. To evaluate novel upstream pathways that regulate placental sFlt1 production, we screened a library of natural compounds ( n =502) in human placental cell lines. Here, we report 3 compounds in the cardiac glycoside family, ouabain, gitoxigenin, and digitoxin, that inhibit placental sFlt1 production at nanomolar concentrations in vitro. We further characterized ouabain and demonstrated that it inhibits sFlt1 mRNA and protein expression in human placental cytotrophoblasts and explant cultures in a dose‐ and time‐dependent manner. Ouabain down‐regulated sFlt1 production by inhibiting hypoxia‐inducible factor 1 (HIF‐1α) protein expression in the placenta. Furthermore, we found that phosphorylation of heat‐shock protein 27 (HSP27) was necessary for ouabain to inhibit HIF‐1α translation. In a rat model of pregnancy‐induced hypertension, ouabain reduced mean arterial pressure and enhanced placental HSP27 phosphorylation without any adverse effects on pups. Further studies are needed to explore the usefulness of targeting HIF‐1α/HSP27 pathway in preeclampsia.—Rana, S., Rajakumar, A., Geahchan, C., Salahuddin, S., Cerdeira, A. S., Burke, S. D., George, E. M., Granger, J. P., Karumanchi, S., A. Ouabain inhibits placental sFlt1 production by repressing HSP27‐dependent HIF‐1α pathway. FASEB J. 28, 4324–4334 (2014). www.fasebj.org